Body Mass Index as a Risk Factor for Diffuse Large B-Cell Lymphoma: A Systematic Review and Meta-Analysis - Vera-Ponce, Víctor Juan; Loayza-Castro, Joan A.; Vásquez-Romero, Luisa Erika Milagros; Zuzunaga-Montoya, Fiorella Elvira (International Journal of Statistics in Medical Research, 2024)
Introduction: Given the increasing prevalence of obesity, as measured by the Body Mass Index (BMI), and the significant impact of Diffuse Large B-cell lymphoma (DLBCL) on global health, it is crucial to update our understanding of the relationship between BMI and DLBCL. Objective: to carry out a systematic review (SR) with meta-analysis to determine the association between DLBCL and BMI Methods: This study is a systematic review and meta-analysis following the PRISMA guidelines. It searched PubMed/Medline, SCOPUS, Web of Science, and EMBASE. The inclusion criteria were primary observational studies involving adults with DLBCL confirmed by biopsy. Exclusions were non-peer-reviewed materials and studies without inferential statistics. The findings of the study are presented as association measures such as relative risks (RR), accompanied by their corresponding 95% confidence intervals (95% CI). Results: From 451 articles, 13 met the criteria for inclusion. The included studies, conducted between 2002 and 2013 in various countries, showed varied follow-up periods and sample sizes. The meta-analysis revealed that individuals with high BMI have a 1.31 times higher risk of developing DLBCL than those with lower BMI (RR: 1.31; 95% CI 1.07, 1.61). The heterogeneity among studies was moderate. Conclusions: The study confirms an association between higher BMI and the increased risk of developing DLBCL. This finding underscores the need to explore further how obesity, chronic inflammation, and the development and progression of DLBCL are interconnected. Understanding this area could significantly reduce DLBCL incidence and improve patient outcomes.